Genetic Polymorphisms of Vascular Endothelial Growth Factor (VEGF) -2549 I/D and +405G/C in the susceptibility to Gastric Cancer - Amar chand Bayal; Shehnaz Sultana; Pratibha Nallari; Venkateshwari Ananthapur (Archives of Clinical Gastroenterology - Peertechz Publications, 2021)
Objective: Vascular Endothelial Growth Factor (VEGF) plays an important role in tumor angiogenesis. Although several studies revealed on association of VEGF polymorphisms with gastric cancer, still the results are inconclusive. The role of (VEGF) -2549 I/D and +405G/C polymorphisms in gastric cancer of Telangana Population is evaluated in the present study. Methods: A case control study was carried out on 540 individuals which comprised of 180 Gastric Cancer patients and 360 healthy control subjects.  The association of functional single nucleotide polymorphisms (SNPs) of the VEGF gene (-2549 I/D and +405G/C) were evaluated by polymerase chain reaction followed by restriction fragment length polymorphism (PCR-RFLP). Results: VEGF -2549 polymorphism with I/D and I/Igenotypeshoweda threefold higher risk (95%CI= 1.75-4.63 and 95%CI= 1.72-5.78) to gastric cancer. A significant association was observed with respect to I allele (AOR= 1.67; 95%CI= 1.29-2.15; P= 7.641e-05) while genotypic and allelic frequencies of VEGF +405G/C polymorphism did not show any significant differences in both the groups.  A significant increase in the frequency of I-G haplotype in Gastric cancer cases was observed compared to control with an AOR of 2.23 (95%CI= (1.51-3.27); P= 0.0001). Conclusion: In conclusion VEGF -2549I/D polymorphism and I-G haplotype conferred significant susceptibility towards gastric cancer, whereas, no such association with respect to +405G/C polymorphism was observed.